Jobs in the circular bioeconomy under scrutiny: the challenging reality of compost production in Rwanda - Surchat, M.; Irakoze, M.; Hansmann, R.; Kantengwa, S.; Konlambigue, Matieyedou; Spath, L.; Wilde, B.; Six, J.; Krutli, P. (Elsevier, 2023)
Today, most African countries have dysfunctional municipal waste management system, negatively impacting the environment and human health. However, as most of this waste is recyclable, informal actors are making their income out of the collection/sorting of waste. Accounting for the risks involved in waste manipulation, it is important to ensure decent working conditions for those recycling it. This study focuses on biowaste recycling in Rwanda, a Circular Economy leader in Africa, with the purpose of: (i) characterizing the working conditions of waste recyclers along the definition of ‘decent work’ and (ii) assessing workers’ satisfaction and its determinants. We surveyed 63 workers employed in three compost production and three biowaste processing companies. Our results show that the work can be considered relatively decent compared to national references, except for insufficient social protections and occupational safety. Workers reported being rather satisfied with their jobs, although our analyses of covariance showed that workers employed in composting were significantly less satisfied than the others. These findings highlight the importance of household-level waste separation for improving not only worker safety, but also nutrient recovery. Further research should investigate how to push forward waste sorting at the household level and improve worker safety (SDG 8) without negatively affecting the women currently employed in waste sorting at the company level (SDG 5).